(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The chemists in the field of drugs and pharmaceuticals have shown interest in benzo fused derivatives of azepines and their analogues1-3.These compounds have extensive applications as anticonvulsants, antianxiety agents, analgesics, and sedatives.